SARS and MERS as learning tools for addressing the 2019-nCoV epidemic: A mini-review - Udit DAVE; Ashwin PALANIAPPAN (Journal of Health and Social Sciences)
The novel Coronavirus (2019-nCoV), named SARS-COV-2, originating in the Wuhan district of China, has reached pandemic proportion with a death toll that is steadily rising. Coronaviruses are classified by their distinct genomic make-up and have been in the spotlight due to their ability to cause fatal epidemics across national borders. Issues such as sub-par personal hygiene, overcrowding, and mass panic exacerbated the spread of the Severe Acute Respiratory Syndrome coronavirus (SARS-CoV) and Middle East Respi- ratory Syndrome coronavirus (MERS-CoV ), serving as crucial lessons for understanding the 2019-nCoV. Heightened sanitation measures with regards to waste disposal in healthcare clinics and in areas of mass transit are also of great importance. The 2019-nCoV is a concern for many different countries and govern- ments of all levels due to its negative effects on public morale, national economies, and health standards and outcomes. There is an immense capacity to use past approaches to SARS and MERS epidemics to influence the design of strategies to control the 2019-nCoV epidemic. The 2019-nCoV has infected more individuals than previous coronaviruses SARS and MERS. In this minireview, we evaluated the SARS and MERS epidemics to provide context to the strategies against 2019-nCoV. We further identified drawbacks in the global approach to combating SARS and MERS to inform policies to curb 2019-nCoV.